Epidemiology of hospital-acquired infections in a tertiary care teaching hospital in India: a cross-sectional study of 79401 inpatients - Narendranath, V.; Nandakumar, B. S.; Sarala, K. S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Healthcare-associated infections are those infections that the patients develop during the course of receiving healthcare treatment for other conditions, which are not incubating at the time of admission. Health care associated infections are the major concerns in the developing countries commonly affecting the ill patients. The purpose of the study is to assess the epidemiology of health care associated infections (HAI) in a tertiary care teaching hospital. Methods: Cross sectional retrospective data was collected for all inpatients from January 2013 to December 2015 covering 79401 inpatients. Data was collected as per ICD – 10 coding, analyzed using SPSS software ver.16. Results: Overall Percentage of different types of HAI calculated, UTI- 1318 (1.66%) more among females and 51.7 %, highest rate in general ward. BSI -360 (0.45%) with 54% male patients, 79.7% medical related type of diagnosis, 66.9% cases from ICU. VAP 148 (0.19%), 62.1% male patients, 94.8%- medical related type of diagnosis. SSI – 30 (0.04%) 65.5% male patients , General Ward 86.2% , 65.5% male patients. Mortality analysis reveal maximum number of deaths was due to BSI contributing to 27.22 % as case fatality rate and 60.12 % proportional mortality rate. Conclusions: Occurrence of hospital acquired infections pose a grave threat to patients as well as health care personnel. Tertiary care centers require a multi-pronged approach to tackle these infections. HAIs lead long term disability, increase in hospital stay, financial burden to the family members. Many a times health care associated infections can be prevented by using standard guidelines, precautions, correct protective measures by health care workers.